Toxic effects of ochratoxin A and citrinin, alone and in combination, on chicken embryos. - Veselá, D (1983)
The embryotoxic potential of ochratoxin A and citrinin was studied after administering, either subgerminally or intraamniotically, single mounting doses of the mycotoxins to chicken embryos on days 2, 3, and 4. The beginning of the embryotoxicity dose range was found to be between 0.01 to 0.05 microgram for ochratoxin A and 1 to 10 micrograms for citrinin. The maximum response to both mycotoxins occurred after administration on day 3. In addition to significant growth retardation of fetuses, exencephaly, microphthalmia, cleft beak, reduction deformities of the limbs, and abdominal wall and ventricular septal defects were encountered on day 8 of incubation. When 4 micrograms of citrinin was constantly added to ochratoxin A administered in the dose range of 0.03 to 0.5 microgram, a strictly additive effect was seen. It may be supposed that citrinin produced together with ochratoxin A in some strains of Penicillium viridicatum Westling does not potentiate the clear-cut embryotoxic action of the latter mycotoxin.